(untitled) (KENOSIS: Jurnal Kajian Teologi, 2024)
The focus of this research is to re-explain ecological problems according to Pope Francis in the encyclical Laudato Si’ articles 101-123, explain eco-literacy according to Fritjof Capra, and explain the correlation of eco-literacy theory with the thinking of Pope Francis. This research aims to summarize and clarify the root causes of ecological problems, find out solutions that can help overcome the root causes of ecological damage caused by the wrong human paradigm in looking at nature, and know the principles of environmental ethics based on the relation of the creation story in the Book of Genesis which breaks the anthropocentrism paradigm in utilizing nature. The method used in this research is discourse analysis of Church documents and several other sources. The primary source used is the Encyclical Laudato Si’ and secondary sources come from several books and scientific journals that discuss ecological issues. The analysis of some of these sources resulted in research findings that the root of ecological problems is caused by the fallacy of the human paradigm towards nature. The solution presented in this research is eco-literacy that can change the anthropocentric human paradigm into an ecotheocentric one, which is a human perspective towards nature that is oriented towards God, the Creator. Thus, humans no longer see nature as their own, but care for and preserve it for God and the common good. Keywords: anthropocentrism, ecology, God, human, nature